Acute myocardial infarction: From diagnosis to intervention (Research, Society and Development, 2022)
Acute Myocardial Infarction is one of the main causes of death in Brazil and in the world. One of the major problems related to the morbidity and mortality of the disease is the time between the onset of symptoms and the beginning of treatment. Thus, the purpose of this narrative review article was to reinforce the importance of early action and pharmacological and non-pharmacological interventions performed in infarcted patients. For this, the search was carried out in the Pubmed, Virtual Health Library, and Sciencedirect databases using the keywords Myocardial Infarction, Acute Myocardial Infarction, ST-Elevation Myocardial Infarction, Myocardial Reperfusion, Reperfusion Injury, and Infarto do Miocardio, Infarto Agudo do Miocardio, ST-Elevation Myocardial Infarction, Myocardial Reperfusion, Reperfusion Injury. Accumulating data show electrocardiography importance at the diagnostic associated with biochemical parameters, and image analysis. The data also reveal the necessity of therapies for irrigation restoration based on anti-aggregating and fibrinolytic. Thus, it reinforces the need to search for medical assistance at the first signs and symptoms, for posterior identification and intervention out in an attempt to maintain the quality of life.